Characteristic Contrast in Δfmin Maps of Organic Molecules Using Atomic Force Microscopy - van der Heijden, Nadine J; Hapala, Prokop; Rombouts, Jeroen A; van der Lit, Joost; Smith, Daniël; Mutombo, Pingo; Švec, Martin; Jelinek, Pavel; Swart, Ingmar (ACS nano, 2016)
Scanning tunneling microscopy and atomic force microscopy can provide detailed information about the geometric and electronic structure of molecules with submolecular spatial resolution. However, an essential capability to realize the full potential of these techniques for chemical applications is missing from the scanning probe toolbox: chemical recognition of organic molecules. Here, we show that maps of the minima of frequency shift-distance curves extracted from 3D data cubes contain characteristic contrast. A detailed theoretical analysis based on density functional theory and molecular mechanics shows that these features are characteristic for the investigated species. Structurally similar but chemically distinct molecules yield significantly different features. We find that the van der Waals and Pauli interaction, together with the specific adsorption geometry of a given molecule on the surface, accounts for the observed contrast.
Keywords: DFT; CO tip; Xe tip; molecular mechanics; AFM; single molecule